Polyamic acid film, rod-shaped silver powder / polyimide composite film and preparation methods thereof

By adding rod-shaped silver powder coated with specific coating agent to the polyamic acid film and using gradient heating heat treatment technology, a rod-shaped silver powder/polyimide composite film with different resistance characteristics was prepared, and the polyimide film was solved. The problem of insufficient charge discharge performance in different scenarios has achieved electrostatic performance that meets different needs.

CN118852696BActive Publication Date: 2025-02-18CHANGCHUN GOLD RES INST
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411321525.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-02-18
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The prior art is difficult to meet the demands of polyimide films for rapid or slow discharge of charge in different scenarios.

Method used

Polyamic acid films were prepared by mixing rod-shaped silver powder coated with vinyl triacetoxysilane and 12-hydroxystearic acid with a polyamic acid solution and heat treatment under vacuum conditions by gradient heating, and at 280 Treatment in a vacuum environment at -300°C to obtain a rod-shaped silver powder/polyimide composite film. The upper and lower surface resistances of the composite film are different, and the surface resistance of the silver powder enriched surface can be adjusted by adjusting the amount of rod-shaped silver powder.

Benefits of technology

The preparation of polyamic acid film and rod-shaped silver powder/polyimide composite film has been achieved, with electrostatic dissipation or electrostatic conductivity, adapting to the needs of different scenarios, and reducing potential risks such as combustion and explosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention provides a polyamic acid film, a rod-shaped silver powder / polyimide composite film and a preparation method thereof, and relates to the field of antistatic materials. The preparation method first prepares a polyamic acid solution and a first silver powder, and then successively coats the first silver powder with vinyl triacetoxysilane and 12-hydroxystearic acid to obtain a second silver powder; finally, the second silver powder is added to the aforementioned polyamic acid solution, a film is formed by a casting method, and then heat-treated to obtain a polyamic acid film with processability. The film is treated in a vacuum environment of 280-300°C for 4-5h to obtain a rod-shaped silver powder / polyimide composite film, the bottom of the composite film is uniformly precipitated and enriched with rod-shaped silver powder, and the silver powders overlap each other to form a three-dimensional mesh conductive structure, so that the upper and lower surfaces of the film have different surface resistances, and the composite film can be applied to electrostatic dissipation or electrostatic conduction according to the surface resistance of the silver powder enriched surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of antistatic materials, and in particular to a polyamic acid film, a rod-shaped silver powder / polyimide composite film and a preparation method thereof. Background Art

[0002] In recent years, polyimide films have been widely used in aerospace, aviation, microelectronics and other fields due to their low dielectric constant and high resistivity, as well as excellent mechanical, thermal and radiation resistance properties. Generally, polyimide has a high surface resistivity and can be used as an electrical insulating material, but it is precisely because of the high surface resistivity that the surface of polyimide is prone to accumulate charges, which can easily cause dangers such as combustion and explosion during use. Therefore, it is of great significance to prepare polyimide films with antistatic properties.

[0003] In the prior art, the patent document with patent number CN113881226B proposes a polyimide antistatic film and a preparation method thereof. In this method, polyaniline is grafted onto graphene and added to the polyimide material as an antistatic agent. The polyaniline molecular chain can stretch and entangle in the polyimide matrix to form an auxiliary conductive path, thereby improving the antistatic effect of the polyimide.

[0004] In the prior art, patent document CN116789998A proposes a method for preparing an antistatic and atomic oxygen resistant polyimide film, which prepares a polyimide film with antistatic and atomic oxygen resistant properties by compounding a conductive filler with an atomic oxygen resistant filler, and mixing the compounded filler with a polyamic acid resin.

[0005] The aforementioned prior arts have successfully prepared polyimide films with antistatic properties, but they are not sufficient to meet the needs of different scenarios. For example, some materials in the operating room need to discharge charges quickly, and some electronic components need to discharge charges slowly.

[0006] In view of this, it is necessary to design an improved polyamic acid film and a rod-shaped silver powder / polyimide composite film made from the polyamic acid film to solve the above problems. Summary of the invention

[0007] The object of the present invention is to provide a polyamic acid film, a rod-shaped silver powder / polyimide composite film and a preparation method thereof. First, a rod-shaped silver powder coated with vinyl triacetoxysilane and 12-hydroxystearic acid is mixed with a polyamic acid solution, and a heat treatment is performed in a gradient heating method under vacuum conditions, so that the rod-shaped silver powder is uniformly precipitated and enriched at the bottom of the film to prepare a polyamic acid film; then, the polyamic acid film is treated in a vacuum environment of 280-300°C for 4-5h to fully imidize the polyamic acid to obtain a rod-shaped silver powder / polyimide composite film. The rod-shaped silver powder overlaps each other at the bottom of the rod-shaped silver powder / polyimide composite film to form a three-dimensional mesh conductive structure, so that the resistance of the upper and lower surfaces is different, which can reduce the potential risks of combustion and explosion during use. The surface resistance of the rod-shaped silver powder / polyimide composite film can be regulated by adjusting the amount of rod-shaped silver powder in the polyamic acid film, so that the rod-shaped silver powder / polyimide composite film has electrostatic dissipation or electrostatic conductivity to meet the needs of different scenarios.

[0008] To achieve the above-mentioned object of the invention, the present invention provides a method for preparing a polyamic acid film, comprising the following steps:

[0009] S1, preparing a polyamic acid solution;

[0010] S2, preparing a first silver powder, dispersing the first silver powder in an ethanol solution of vinyl triacetoxysilane, stirring, filtering, and then dispersing the first silver powder in an ethanol solution of 12-hydroxystearic acid, stirring, filtering, and drying to obtain a second silver powder; the amount of the vinyl triacetoxysilane is 0.05-0.1% of the mass of the first silver powder, and the amount of the 12-hydroxystearic acid is 0.1-0.2% of the mass of the first silver powder;

[0011] S3, taking the second silver powder obtained in step S2 and adding it to the polyamic acid solution prepared in step S1, pouring the mixture evenly on glass after mixing, forming a film by a casting method, and then heat-treating the film by a gradient heating method under vacuum conditions, first heating at a certain heating rate, and when the temperature rises to 50°C, 70°C, 90°C, 120°C, and 150°C, maintaining the temperature for 1.9-2.1h and then continuing to heat, so as to obtain a polyamic acid film; the amount of the second silver powder is 1-5% of the mass of the polyamic acid.

[0012] As a further improvement of the present invention, in step S1, the preparation method of the polyamic acid solution is to take a predetermined amount of 4,4-diaminodiphenyl ether and dimethylacetamide, mix and stir, wait for them to be fully dissolved, slowly add a certain amount of pyromellitic anhydride, pass nitrogen protection, stir and react for 2 hours in an ice-water bath to obtain the polyamic acid solution; wherein the mass ratio of the 4,4-diaminodiphenyl ether, the dimethylacetamide and the pyromellitic anhydride is (1-1.5):(6-9):(1.09-1.64).

[0013] As a further improvement of the present invention, in step S2, the preparation method of the first silver powder is to take a predetermined amount of deionized water, silver nitrate, and polyvinyl pyrrolidone, mix and stir evenly, add ammonia water until the solution is clarified, add a certain amount of sodium hydroxide, and add ammonia water again until the solution is clarified to obtain a mixed solution; then, under a constant temperature condition of 0-25°C, slowly add a certain amount of formalin to the mixed solution and stir it thoroughly, then add a certain amount of stearic acid ethanol solution with a mass concentration of 0.5-1%, mix evenly, filter, and wash to obtain the first silver powder; the mass ratio of the silver nitrate to the polyvinyl pyrrolidone is (5-6): (0.2-0.3), the mass ratio of the silver nitrate to the sodium hydroxide is (5-6): (0-0.05), and the mass ratio of the silver nitrate to the formalin is (5-6): (10-15).

[0014] As a further improvement of the present invention, in step S2, the stirring times for both times are 10-15 minutes.

[0015] The present invention also provides a polyamic acid film, which is prepared according to the preparation method described in any one of the above technical solutions.

[0016] The present invention also provides a method for preparing a rod-shaped silver powder / polyimide composite film, specifically, placing the polyamic acid film obtained by any of the aforementioned technical schemes in a vacuum environment at 280-300°C for 4-5 hours to obtain the rod-shaped silver powder / polyimide composite film.

[0017] The present invention also provides a rod-shaped silver powder / polyimide composite film, which is prepared by the preparation method described in the above technical solution.

[0018] As a further improvement of the present invention, the surface resistances of the two sides of the rod-shaped silver powder / polyimide composite film are different, wherein the A side is enriched with silver powder and the B side is not enriched with silver powder.

[0019] As a further improvement of the present invention, the surface resistance of the A surface is 4×10 4 Ω-7×10 7Ω, the surface resistance of the B surface is 5×10 13 Ω-9×10 13 Ω.

[0020] The beneficial effects of the present invention are:

[0021] The present invention provides a polyamic acid film, a rod-shaped silver powder / polyimide composite film and a preparation method thereof. First, a rod-shaped silver powder coated with vinyl triacetoxysilane and 12-hydroxystearic acid is mixed with a polyamic acid solution, and heat-treated by a gradient heating method under vacuum conditions, so that the rod-shaped silver powder is uniformly precipitated and enriched at the bottom of the film, and a polyamic acid film is prepared, and the polyamic acid film has processability; then, the polyamic acid film is treated in a vacuum environment of 280-300°C for 4-5h to fully imidize the polyamic acid, and a rod-shaped silver powder / polyimide composite film is prepared. The rod-shaped silver powder at the bottom of the rod-shaped silver powder / polyimide composite film overlaps with each other to form a three-dimensional mesh conductive structure, so that the resistance of the upper and lower surfaces is different, and the surface resistance of the silver powder enriched surface can be regulated by adjusting the amount of rod-shaped silver powder in the polyamic acid film.

[0022] (1) The surface resistances of the upper and lower surfaces of the rod-shaped silver powder / polyimide composite film prepared by the present invention are different, wherein the surface resistance of the silver powder-enriched surface is 4×10 4 Ω-7×10 7 Ω, the surface resistance of the other side is 5×10 13 Ω-9×10 13 Ω, in practical applications, the composite film coating material can be used to close the silver powder-enriched side with lower surface resistance to the material, and the other side with higher surface resistance can be exposed. The silver powder-enriched side can have an antistatic effect, while the exposed side still retains the original electrical insulation properties of the polyimide film. This arrangement can make it difficult for charge to accumulate on the film surface, thereby reducing potential risks such as combustion and explosion during use.

[0023] (2) In the preparation method provided by the present invention, the surface resistance of the silver powder-enriched surface of the rod-shaped silver powder / polyimide composite film can be adjusted by adjusting the amount of rod-shaped silver powder in the polyamic acid film to prepare rod-shaped silver powder / polyimide composite films with different antistatic properties. For example, when the amount of silver powder is 1.5% by weight of the polyamic acid, the surface resistance of the silver powder-enriched surface is 3.2×10 7 Ω, indicating that the composite film has electrostatic dissipation performance and can be used in electronic components that need to slowly discharge charge; when the amount of silver powder is 4.5% of the mass of polyamic acid, the surface resistance of the silver powder enriched surface is 4.7×10 4 Ω, indicating that the composite film has electrostatic conductive properties and can be used in materials that require rapid charge discharge.

[0024] (3) The present invention uses two different coating agents, vinyl triacetoxysilane and 12-hydroxystearic acid, to coat the rod-shaped silver powder, and the amount of vinyl triacetoxysilane is controlled to 0.05-0.1% of the mass of silver, and the amount of 12-hydroxystearic acid is controlled to 0.1-0.2% of the mass of silver powder. Among them, the alkoxy group in vinyl triacetoxysilane can be hydrolyzed into silanol, which reacts with the hydroxyl group in polyamic acid to form hydrogen bonds, thereby increasing the affinity between silver powder and polyamic acid; and 12-hydroxystearic acid can synergistically act with vinyl triacetoxysilane, while ensuring the dispersibility of silver powder, it also reduces the affinity of part of silver powder to polyamic acid, so that the silver powder can gradually settle in the polyamic acid and be evenly dispersed at the bottom of the polyamic acid.

[0025] (4) The present invention adopts a gradient heating method for heat treatment to prepare a polyamic acid film. Specifically, the temperature is first increased at a certain heating rate. When the temperature rises to 50°C, 70°C, 90°C, 120°C, and 150°C, the temperature is maintained for 1.9-2.1 hours before continuing to increase the temperature. This arrangement can not only allow the silver powder to fully settle and accumulate at the bottom of the film, but also allow the solvent to evaporate slowly, avoiding bubbles on the film surface when the solvent escapes too quickly. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below in conjunction with specific embodiments.

[0027] It should be noted here that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0028] The present invention provides a method for preparing a polyamic acid film, comprising the following steps:

[0029] S1, preparing a polyamic acid solution;

[0030] Specifically, the preparation method of the polyamic acid solution is to take a predetermined amount of 4,4-diaminodiphenyl ether and dimethylacetamide, mix and stir, wait for them to be fully dissolved, slowly add a certain amount of pyromellitic anhydride, pass nitrogen protection, stir and react for 2 hours in an ice water bath to obtain a polyamic acid solution; wherein the mass ratio of 4,4-diaminodiphenyl ether, dimethylacetamide and pyromellitic anhydride is (1-1.5): (6-9): (1.09-1.64).

[0031] S2, preparing a first silver powder, dispersing the first silver powder in an ethanol solution of vinyl triacetoxysilane, stirring, filtering, and then dispersing the first silver powder in an ethanol solution of 12-hydroxystearic acid, stirring, filtering, and drying to obtain a second silver powder, i.e., a coated rod-shaped silver powder; the amount of the vinyl triacetoxysilane is 0.05-0.1% of the mass of the first silver powder, and the amount of the 12-hydroxystearic acid is 0.1-0.2% of the mass of the first silver powder;

[0032] Specifically, the stirring time for both times is 10-15 minutes.

[0033] Specifically, the preparation method of the first silver powder is to take a predetermined amount of deionized water, silver nitrate, and polyvinyl pyrrolidone (PVP), mix and stir evenly, add ammonia water until the solution is clarified, add a certain amount of sodium hydroxide, and add ammonia water again until the solution is clarified to obtain a mixed solution; then, under a constant temperature condition of 0-25°C, slowly add a certain amount of formalin to the mixed solution and stir it thoroughly, then add a certain amount of stearic acid ethanol solution with a mass concentration of 0.5-1%, mix evenly, filter, and wash to obtain the first silver powder; the mass ratio of silver nitrate to polyvinyl pyrrolidone is (5-6): (0.2-0.3), the mass ratio of silver nitrate to sodium hydroxide is (5-6): (0-0.05), and the mass ratio of silver nitrate to formalin is (5-6): (10-15); the model of PVP is K30; the washing process is to use deionized water to wash until the pH of the silver powder surface is neutral; preferably, the dripping speed of formalin is 3mL / min.

[0034] The amount of vinyl triacetoxysilane used must be controlled within a certain range. If the amount is too much, the affinity of the rod-shaped silver powder to polyamic acid will be too high, making it difficult to settle. If the amount is too little, the rod-shaped silver powder will be difficult to disperse evenly in the polyamic acid.

[0035] Vinyl triacetoxysilane and 12-hydroxystearic acid act synergistically to reduce the affinity of a portion of the rod-shaped silver powder to polyamic acid while ensuring the dispersibility of the rod-shaped silver powder, so that the rod-shaped silver powder can gradually settle in the polyamic acid and be evenly dispersed at the bottom of the polyamic acid. Therefore, when only vinyl triacetoxysilane or only 12-hydroxystearic acid is used to coat the rod-shaped silver powder, the obtained polyamic acid film cannot prepare a rod-shaped silver powder / polyimide composite film with antistatic properties.

[0036] S3, taking the second silver powder obtained in step S2 and adding it to the polyamic acid solution prepared in step S1, pouring the mixture evenly on the glass after mixing, forming a film by a casting method, and then heat-treating it by a gradient heating method under vacuum conditions, first heating at a certain heating rate, and when the temperature rises to 50°C, 70°C, 90°C, 120°C, and 150°C, the temperature is maintained for 1.9-2.1h and then continued to heat up to obtain a polyamic acid film; the amount of the second silver powder is 1-5% of the mass of the polyamic acid, and by adjusting the amount of silver powder, the rod-shaped silver powder / polyimide composite film can have electrostatic dissipation or electrostatic conductivity to meet the needs of different scenarios.

[0037] More specifically, the gradient heating method is to use a vacuum constant temperature drying oven to first raise the temperature to 50°C, keep it warm for 2 hours, then raise the temperature to 70°C, keep it warm for 2 hours, then raise the temperature to 90°C, keep it warm for 2 hours, continue to raise the temperature to 120°C, keep it warm for 2 hours, and finally raise the temperature to 150°C, and keep it warm for 2 hours.

[0038] During the heat treatment, the initial heating rate cannot be too fast. A gradient heating process is set up to allow the silver powder to fully settle and accumulate at the bottom of the polyamic acid film, while allowing the solvent to evaporate slowly to avoid leaving bubbles on the film surface when the solvent escapes too quickly.

[0039] The purity of the ethanol used in the above technical solutions is 98%.

[0040] The present invention provides a polyamic acid film, which is prepared by the preparation method described in any one of the above technical solutions.

[0041] The present invention also provides a method for preparing a rod-shaped silver powder / polyimide composite film. The rod-shaped silver powder / polyimide composite film is prepared by placing a polyamic acid film in a vacuum environment at 280-300° C. for 4-5 hours.

[0042] The present invention also provides a rod-shaped silver powder / polyimide composite film, which is prepared by the preparation method described in the above technical solution. More specifically, the surface resistance of the two sides of the rod-shaped silver powder / polyimide composite film is different, wherein the A side is enriched with silver powder, and the B side is not enriched with silver powder. The surface resistance of the A side is 4×10 4 Ω-7×10 7 Ω, the surface resistance of surface B is 5×10 13 Ω-9×10 13 Ω.

[0043] Those skilled in the art should understand that the polyamic acid film provided by the present invention can also be processed by other methods to obtain other products not limited to rod-shaped silver powder / polyimide composite films.

[0044] The following describes the method for preparing the polyamic acid film and the method for preparing the rod-shaped silver powder / polyimide composite film provided by the present invention in conjunction with specific embodiments.

[0045] Example 1

[0046] Example 1 provides a method for preparing a polyamic acid film and a method for preparing a rod-shaped silver powder / polyimide composite film.

[0047] The method for preparing the polyamic acid film provided in this embodiment specifically comprises the following steps:

[0048] S1, add 10g 4.4-diaminodiphenyl ether and 60g dimethylacetamide into a three-necked flask, stir until completely dissolved, slowly add 10.9g pyromellitic dianhydride, and pass nitrogen protection, place the reaction system in an ice water bath and stir for 2h to obtain a polyamic acid solution.

[0049] S2, preparing a first silver powder, and coating the first silver powder to obtain a second silver powder.

[0050] S2.1, under mechanical stirring, add 5.5g of silver nitrate to 100mL of deionized water, add 0.3g of PVP after thorough mixing, and after PVP is fully dissolved, add ammonia water until the solution is clear, then add 0.01g of sodium hydroxide and mix thoroughly, and then continue to add ammonia water until the solution is clear to obtain a silver solution. Then, place the silver solution at a constant temperature of 25°C and mechanical stirring, slowly drip 10g of formalin into the solution at a drip rate of 3mL / min, continue stirring for 1min, add 5mL of 0.5% stearic acid ethanol solution, mix well, filter, wash with deionized water until the pH of the silver powder surface is neutral, filter, and obtain the first silver powder.

[0051] S2.2, disperse the first silver powder obtained in step S2.1 in a 0.5% mass concentration of vinyl triacetoxysilane-ethanol solution, wherein the mass of vinyl triacetoxysilane is 0.05% of the mass of the silver powder, then stir for 15 minutes, filter, and then disperse the filtered silver powder in a 0.5% mass concentration of 12-hydroxystearic acid ethanol solution, wherein the amount of 12-hydroxystearic acid is 0.1% of the mass of the silver powder, continue stirring for 15 minutes, filter, and dry to obtain the second silver powder, that is, the coated rod-shaped silver powder.

[0052] S3, weigh 10g of the polyamic acid solution obtained in step S1, add a second silver powder, the mass of the silver powder is 1.5% of the mass of the polyamic acid, mix well, pour the solution evenly on a glass plate, form a film by a casting method, and put it into a vacuum constant temperature drying oven, increase the temperature gradually for heat treatment, when the temperature rises to 50°C, 70°C, 90°C, 120°C, and 150°C, maintain the temperature for 2h and then continue to increase the temperature to obtain a polyamic acid film.

[0053] The method for preparing the rod-shaped silver powder / polyimide composite film provided in this embodiment is as follows: the polyamic acid film prepared in steps S1-S3 is placed in a vacuum environment at 280-300° C. for 4-5 hours to obtain the rod-shaped silver powder / polyimide composite film.

[0054] The resistance of the rod-shaped silver powder / polyimide composite film prepared in this example was tested, wherein the surface resistance of the silver powder enriched surface was 3.2×10 7 Ω, and the surface resistance of the other side is 6.3×10 13 Ω, which meets the requirements of static dissipative materials.

[0055] Example 2

[0056] The difference between Example 2 and Example 1 is that in step S3, the mass of the added rod-shaped silver powder is 4.5% of the mass of the polyamic acid, and the rest is substantially the same as Example 1 and will not be described herein.

[0057] The resistance of the rod-shaped silver powder / polyimide composite film prepared in this example was tested, wherein the surface resistance of the silver powder enriched surface was 4.7×10 4 Ω, and the surface resistance of the other side is 7.1×10 13 Ω, which meets the requirements of electrostatic conductive materials.

[0058] Example 3

[0059] The difference between Example 3 and Example 1 is that in step S2.2, the amount of vinyl triacetoxy silane used is 0.1% of the mass of the silver powder, and the rest is substantially the same as Example 1 and will not be repeated here.

[0060] The resistance of the rod-shaped silver powder / polyimide composite film prepared in this example was tested, wherein the surface resistance of the silver powder enriched surface was 6.2×10 7 Ω, and the surface resistance of the other side is 6.5×10 13 Ω, which meets the requirements of static dissipative materials.

[0061] Comparative Example 1

[0062] The difference between Comparative Example 1 and Example 1 is that in the preparation method of the polyamic acid film, no rod-shaped silver powder is added, and specifically comprises the following steps:

[0063] S1, add 10g 4.4-diaminodiphenyl ether and 60g dimethylacetamide into a three-necked flask, stir until completely dissolved, slowly add 10.9g pyromellitic dianhydride, and pass nitrogen protection, place the reaction system in an ice water bath and stir for 2h to obtain a polyamic acid solution.

[0064] S2, weigh 10g of the polyamic acid solution obtained in step S1 and pour it on a glass plate, form a film by a casting method, and put it into a vacuum constant temperature drying oven for heat treatment, and increase the temperature gradually for heat treatment. When the temperature rises to 50°C, 70°C, 90°C, 120°C, and 150°C, maintain the temperature for 2h and then continue to increase the temperature to obtain a polyamic acid film.

[0065] The method for preparing the polyimide film provided in this comparative example is: placing the polyamic acid film prepared in steps S1-S2 in a vacuum environment at 280-300° C. for 4-5 hours to obtain the polyimide film.

[0066] The resistance of the polyimide film prepared in this comparative example was tested, and the surface resistance of one side was 7.1×10 13 Ω, and the surface resistance of the other side is 7.5×10 13 Ω, does not meet the anti-static requirements.

[0067] Comparative Example 2

[0068] The difference between Comparative Example 2 and Example 1 is that in step S3, the mass of the added rod-shaped silver powder is 0.5% of the mass of the polyamic acid, and the other parts are substantially the same as those in Example 1 and will not be described herein.

[0069] The resistance of the rod-shaped silver powder / polyimide composite film prepared in this comparative example was tested, wherein the surface resistance of the silver powder enriched surface was 6.9×10 13 Ω, and the surface resistance of the other side is 7.5×10 13 Ω, indicating that the composite film prepared in this comparative example does not have the function of electrostatic discharge. This is because too little silver powder cannot be evenly enriched on the surface of the film and cannot form a conductive path.

[0070] Comparative Example 3

[0071] The difference between Comparative Example 3 and Example 1 is that in step S3, the mass of the added rod-shaped silver powder is 10% of the mass of the polyamic acid, and the other details are substantially the same as those in Example 1 and will not be described herein.

[0072] The rod-shaped silver powder / polyimide composite film prepared in this comparative example has very poor mechanical properties and cannot be tested.

[0073] Comparative Example 4

[0074] The difference between Comparative Example 4 and Example 1 is that in step S2.2, the surface treatment of the silver powder uses only vinyl triacetoxy silane, and no 12-hydroxystearic acid is added. The amount of vinyl triacetoxy silane is 0.05% of the mass of the silver powder. The rest is the same as Example 1 and will not be repeated here.

[0075] The resistance of the rod-shaped silver powder / polyimide composite film prepared in this comparative example was tested, wherein the surface resistance of the silver powder enriched surface was 4.2×10 13 Ω, and the surface resistance of the other side is 6.5×10 13 Ω, indicating that the composite film does not have the function of electrostatic discharge.

[0076] Comparative Example 5

[0077] The difference between Comparative Example 5 and Example 1 is that in step S2.2, the amount of vinyl triacetoxysilane used is 2% of the mass of the silver powder, and the rest is substantially the same as Example 1 and will not be repeated here.

[0078] The resistance of the rod-shaped silver powder / polyimide composite film prepared in this comparative example was tested, wherein the surface resistance of the silver powder enriched surface was 2.6×10 13 Ω, and the surface resistance of the other side is 5.5×10 13 Ω, indicating that the composite film does not have the function of electrostatic discharge.

[0079] Comparative Example 6

[0080] The difference between Comparative Example 6 and Example 1 is that in step S2.2, only 12-hydroxystearic acid is used for the surface treatment of the silver powder, and no vinyl triacetoxysilane is added. The amount of 12-hydroxystearic acid used is 0.1% of the mass of the silver powder. The rest is roughly the same as Example 1 and will not be repeated here.

[0081] The silver powder prepared in this comparative example cannot be dispersed in the polyamic acid solution, and there is no point in testing the resistance.

[0082] The contact angles of the rod-shaped silver powders prepared in Example 1, Example 3 and Comparative Examples 4-6 were tested. The testing method was as follows: a small amount of rod-shaped silver powder was pressed into a sheet, and a polyamic acid solution was dropped onto the surface of the silver powder to test the contact angle. The measured contact angles are shown in the table below.

[0083]

[0084] Please refer to the table above. By comparison, it can be seen that the coating effect of vinyl triacetoxysilane reduces the contact angle of silver powder, while the coating effect of 12-hydroxystearic acid increases the contact angle of silver powder. The synergistic effect of the two coating agents can adjust the contact angle of silver powder to a suitable intermediate value, which is conducive to the subsequent uniform dispersion and sedimentation of silver powder in the polyamic acid solution.

[0085] Next, the mechanical properties of the rod-shaped silver powder / polyimide composite films prepared in Examples 1-3, Comparative Example 2, and Comparative Examples 4-6 were tested. For the convenience of comparison, the tensile strength (MPa), surface resistance (Ω), coating agent dosage, and silver powder dosage obtained from the test are summarized in the following table, where side A is the silver powder enriched side, side B is not silver powder enriched, and in Comparative Example 1, no silver powder is added, so the side with smaller surface resistance is taken as side A.

[0086]

[0087] Please refer to the table above, and you can see that there is a difference in the resistance of the upper and lower surfaces of the rod-shaped silver powder / polyimide composite film provided by the present invention. This is because, when the polyamic acid film is prepared by heat treatment, the rod-shaped silver powder is uniformly settled and enriched at the bottom of the film under the action of gravity, and overlaps with each other to form a three-dimensional mesh conductive structure. The polyamic acid film is used to prepare the rod-shaped silver powder / polyimide composite film, which can greatly reduce the resistance of the silver powder-enriched surface of the rod-shaped silver powder / polyimide composite film. In practical applications, the rod-shaped silver powder / polyimide composite film is used to coat the material, and the silver powder-enriched surface with a lower surface resistance can be closely attached to the material, and the other side with a higher surface resistance is exposed to the outside. The silver powder-enriched surface can have an antistatic effect, and the exposed side still retains the original electrical insulation properties of the polyimide film. Such a setting can make it difficult for the film surface to accumulate charge, so as to reduce the potential risks of combustion and explosion during use.

[0088] By comparing Examples 1-2 and Comparative Examples 1-3, it can be seen that different silver powder contents can make the rod-shaped silver powder / polyimide composite film present different properties, such as the film prepared in Example 1 has electrostatic dissipation properties, and the film prepared in Example 2 has electrostatic conductivity properties. However, when the silver powder content is too little, the silver powder cannot be evenly enriched on the surface of the film, and thus cannot form a conductive path, so that the rod-shaped silver powder / polyimide composite film does not have the function of electrostatic conduction; when the amount of silver powder is too much, the excess silver powder settles at the bottom of the film, which will destroy the original mechanical properties of the film and cannot be used in practice.

[0089] Comparing Example 1 with Comparative Examples 4-6, it can be seen that the amount of vinyl triacetoxysilane used is too much or too little, or only one of vinyl triacetoxysilane and 12-hydroxystearic acid is used for coating, which will cause the obtained rod-shaped silver powder / polyimide composite film to not have the performance of electrostatic derivation. This is because the alkoxy group in vinyl triacetoxysilane can be hydrolyzed into silanol, which reacts with the hydroxyl group in polyamic acid to form hydrogen bonds, thereby increasing the affinity of silver powder and polyamic acid, and only using vinyl triacetoxysilane will make this affinity too high, resulting in silver powder being difficult to settle in polyamic acid; 12-hydroxystearic acid can work synergistically with vinyl triacetoxysilane, while ensuring the dispersibility of silver powder, reducing the affinity of a part of silver powder to polyamic acid, so that silver powder can gradually settle in polyamic acid and be evenly dispersed at the bottom of polyamic acid, while only using 12-hydroxystearic acid will make it difficult for silver powder to be evenly dispersed in polyamic acid.

[0090] In summary, the present invention uses vinyl triacetoxysilane and 12-hydroxystearic acid to coat the rod-shaped silver powder, and by adjusting the amount of the coating agent, the amount of vinyl triacetoxysilane is preferably 0.05-0.1% of the mass of the silver powder, and the amount of 12-hydroxystearic acid is preferably 0.1-0.2% of the mass of the silver powder, so that the silver powder can be uniformly precipitated and enriched at the bottom during the composite process with polyamic acid, and a polyamic acid film is prepared, and then a rod-shaped silver powder / polyimide composite film with electrostatic desorption function is prepared by further treating the polyamic acid film, and the surface resistance of the upper and lower surfaces of the composite film is different, wherein the surface resistance of the silver powder enriched surface is 4×10 4 Ω-7×10 7 Ω, the surface resistance of the other side is 5×10 13 Ω-9×10 13 Ω.

[0091] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a polyamic acid film, characterized in that: The following steps are involved: S1, preparing a polyamic acid solution; S2, preparing a first silver powder, dispersing the first silver powder in an ethanol solution of vinyl triacetoxysilane, stirring, filtering, and then dispersing the first silver powder in an ethanol solution of 12-hydroxystearic acid, stirring, filtering, and drying to obtain a second silver powder; the amount of the vinyl triacetoxysilane is 0.05-0.1% of the mass of the first silver powder, and the amount of the 12-hydroxystearic acid is 0.1-0.2% of the mass of the first silver powder; S3, taking the second silver powder obtained in step S2 and adding it to the polyamic acid solution prepared in step S1, pouring the mixture evenly on glass after mixing, forming a film by a casting method, and then heat-treating the film by a gradient heating method under vacuum conditions, first heating at a certain heating rate, and when the temperature rises to 50°C, 70°C, 90°C, 120°C, and 150°C, maintaining the temperature for 1.9-2.1h and then continuing to heat, so as to obtain a polyamic acid film; the amount of the second silver powder is 1-5% of the mass of the polyamic acid.

2. The method for preparing a polyamic acid film according to claim 1, wherein: In step S1, the preparation method of the polyamic acid solution is to take a predetermined amount of 4,4-diaminodiphenyl ether and dimethylacetamide, mix and stir, wait for them to be fully dissolved, slowly add a certain amount of pyromellitic anhydride, pass nitrogen protection, stir and react for 2 hours in an ice water bath to obtain the polyamic acid solution; wherein the mass ratio of the 4,4-diaminodiphenyl ether, the dimethylacetamide, and the pyromellitic anhydride is (1-1.5): (6-9): (1.09-1.64).

3. The method for preparing a polyamic acid film according to claim 1, wherein: In step S2, the preparation method of the first silver powder is to take a predetermined amount of deionized water, silver nitrate, and polyvinyl pyrrolidone, mix and stir evenly, add ammonia water until the solution is clarified, add a certain amount of sodium hydroxide, and add ammonia water again until the solution is clarified to obtain a mixed solution; then, under a constant temperature condition of 0-25°C, slowly add a certain amount of formalin to the mixed solution and stir it thoroughly, then add a certain amount of stearic acid ethanol solution with a mass concentration of 0.5-1%, mix evenly, filter, and wash to obtain the first silver powder; the mass ratio of the silver nitrate to the polyvinyl pyrrolidone is (5-6): (0.2-0.3), the mass ratio of the silver nitrate to the sodium hydroxide is (5-6): (0-0.05), and the mass ratio of the silver nitrate to the formalin is (5-6): (10-15).

4. The method for preparing a polyamic acid film according to claim 3, wherein: In step S2, the stirring time for both times is 10-15 min.

5. A polyamic acid film, characterized in that: The polyamic acid film is prepared according to the preparation method described in any one of claims 1 to 4.

6. A method for preparing a rod-shaped silver powder / polyimide composite film, characterized in that: The polyamic acid film prepared by any one of claims 1 to 4 or the polyamic acid film provided by claim 5 is placed in a vacuum environment at 280-300° C. for 4-5 hours to obtain a rod-shaped silver powder / polyimide composite film.

7. A rod-shaped silver powder / polyimide composite film, characterized in that: The rod-shaped silver powder / polyimide composite film Prepared according to the preparation method according to claim 6.

8. The rod-shaped silver powder / polyimide composite film according to claim 7, characterized in that: The surface resistances of the two sides of the rod-shaped silver powder / polyimide composite film are different, wherein the A side is enriched with silver powder, and the B side is not enriched with silver powder.

9. The rod-shaped silver powder / polyimide composite film according to claim 8, characterized in that: The surface resistance of the A surface is 4×10 4 Ω-7×10 7 Ω, the surface resistance of the B surface is 5×10 13 Ω-9×10 13 Ω.

Citation Information

Patent Citations

  • A polyimide antistatic film and its preparation method

    CN113881226B

  • Antistatic atomic oxygen-resistant polyimide film and preparation method thereof

    CN116789998A

  • Cosmetic method using a composition comprising a siloxane resin and a mineral filler

    CN101951992A

  • Thermoplastic resin composition and film made from the composition

    CN1213391A